Decoy peptides derived from the extracellular domain of toll-like receptor 2 (TLR2) show anti-inflammatory properties. Issue 16 (1st September 2018) - Ebner, S.; Trieb, M.; Schönfeld, M.; Wietzorrek, G.; Santos-Sierra, S.
Graphical abstract: Abstract: Toll-like receptor 2 (TLR2) recognizes bacterial derived- and synthetic-lipopeptides after dimerization with TLR1 or TLR6. Hyper-activation of TLR2 has been described in several inflammatory diseases and the discovery of inhibitors of its pro-inflammatory activity represent potential starting points to develop therapeutics in such pathologies. We designed peptides derived from the TLR2 sequence comprising amino acid residues involved in ligand binding (Pam3CSK4) or heterodimerization (TLR2/TLR1) as pointed out by structural data. 2 We identified several peptides (P13, P13(LL), P16, P16(LL)) which inhibited TLR2/1 signaling in HEK293-TLR2 cells (MAPK activation and NF-kB activity). Moreover, P13L and P16L decreased TNFα release in human primary PBMCs and mouse macrophages. The peptides were selective for TLR2/1 as they did not inhibit the activity of other TLRs tested. P13L and P16L inhibited the internalization of Pam3CSK4 fluorescently labeled in macrophages and the heterodimerization of TLR2 with TLR1 as demonstrated by immunoprecipitation studies. Our data demonstrate that peptides derived from the region comprising the leucine-rich repeats (LRR) 11 and 13 in the extracellular domain of TLR2 are good starting points to develop more potent anti-inflammatory peptides with TLR2 inhibitory activity.